Comprehending the responsible tourism practices through principles of sustainability: A case of Kinabalu Park - Tay, Kai Xin; Chan, Jennifer Kim Lian; Christine A. Vogt; Badaruddin Mohamed (Elsevier, 2016)
This study initiates a research into the practices of responsible tourism in the UNESCO National Park, a place with high levels of biodiversity and value that is worthy of preservation. The responsible tourism definitions, practices and challenges emerged through an intense scrutiny of textual data, which were collected through in-depth interviews with 25 tour operators and park management. Results indicated that responsibility was constructed around the principles of sustainability, or a reification of, ecological friendliness, economical viability and sociocultural amicability in Kinabalu Park, Sabah. Finally, the paper exemplified three implication practices to boost responsible tourism development in Kinabalu Park and other similar parks.